2022
DOI: 10.1007/s00442-022-05189-6
|View full text |Cite
|
Sign up to set email alerts
|

Costs and benefits of “insect friendly” artificial lights are taxon specific

Abstract: The expansion of human activity into natural habitats often results in the introduction of arti cial light at night, which can disrupt local ecosystems. Recent advances in LED technology have enabled spectral tuning of arti cial light sources, which could in theory limit their impact on vulnerable taxa. To date, however, experimental comparisons of ecologically friendly candidate colors have mostly considered only one type of behavioral impact, often on only single species. Resulting recommendations cannot be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…Crepuscular fireflies are adapted to engage in courtship and mating under ambient light and may therefore be more resilient to the introduction of ALAN into their habitat [ 78 ], perhaps even benefitting from an artificially extended twilight. Such pattern is already emerging from studies measuring the impact of ALAN on male courtship flash activity in different species (reviewed in [ 38 ]). However, whether this pattern is also reflected in its impacts on mate success remains to be conclusively demonstrated.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Crepuscular fireflies are adapted to engage in courtship and mating under ambient light and may therefore be more resilient to the introduction of ALAN into their habitat [ 78 ], perhaps even benefitting from an artificially extended twilight. Such pattern is already emerging from studies measuring the impact of ALAN on male courtship flash activity in different species (reviewed in [ 38 ]). However, whether this pattern is also reflected in its impacts on mate success remains to be conclusively demonstrated.…”
Section: Discussionmentioning
confidence: 91%
“…Recent research on flashing fireflies has found that patrolling males are less abundant [ 37 , 38 ] and/or less active [ 18 , 39 , 40 ] near artificial lights. Stationary female fireflies under artificial lights are even more strongly affected, rarely if ever answering nearby male advertisements [ 18 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fascinating flash behavior in fireflies has attracted attention since antiquity. However, because of increasing urbanization and pollution [3][4][5][6][7][8][9], the populations of many species of fireflies have been declining [10,11]. The firefly Pyrocoelia pectoralis (Olivier) (Lampyridae: Lampyrinae) has terrestrial larvae and is endemic to China, where its populations have decreased alarmingly; it was listed as a protected animal for the first time in June 2023 (http://www.forestry.gov.cn/c/www/gsgg/509640.jhtml, accessed on 30 June 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The phototropism of insects might significantly differ among orders. Some insects (such as most Lepidoptera and Hymenoptera) with broad visual sensitivity can be attracted to artificial light at wavelengths of 300-700 nm (Briscoe and Chittka, 2001;van der Kooi et al, 2021), whereas some flying insects are attracted to long-wave visible light, such as amber lights (610.72 ± 47.88 nm) (Owens et al, 2022a). The insect species and artificial light (spectral distribution and light intensity) determine the extent to which insects are attracted to artificial light.…”
Section: Introductionmentioning
confidence: 99%